The association between flat feet and body mass index in the adult population: a systematic review - Mohd Dar, Shahid; Fauzi, Aisyah Fakhriah (IIUM Press, 2023)
Background: Flat foot is one of the foot disorders that is usually neglected which may seriously affect the quality of life in a longer term. Among the etiological factors, one of those is the higher body mass index (BMI). While flat foot incidence is common, its relationship with body mass index remains equivocal. Aim: This systematic review investigated the association between flat feet and body mass index in the adult population. Methods: A systematic search of three electronic databases was conducted. Studies on human adults (>18 years) with flat feet and gold standard outcome measures were included. This review was conducted and reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The Appraisal tool for Cros-Sectional Studies (AXIS) was utilised to assess the methodological quality. All articles had good score of methodological quality. Results: Out of the 720 articles that were screened, only eight studies met the inclusion criteria and were included in this systematic review. From these eight articles, seven studies reported a significant relationship between flat feet and body mass index in the adult population. Conclusion: There is a significant association between flat feet and body mass index among the adult population. Therefore, as the BMI increases, the chances of developing flat foot increases.